Waterbird community changes in the Wilderness Lakes, South Africa (Part 1 of 3): Herbivores and omnivores - Ian A. Russell (Koedoe: African Protected Area Conservation and Science, 2023)
Global and regional degradation and loss of aquatic systems can negatively affect wetland-dependent waterbirds. The Wilderness Lakes Complex in South Africa, which incorporates the Wilderness Ramsar site, supports populations of 68 waterbird species including eight which periodically occur in globally significant (1% population) numbers. The study aimed to document long-term spatial and temporal (including seasonal) patterns of abundance of herbivorous waterbirds in the Wilderness Lakes Complex, and where possible identify potential causes for observed trends. The abundance of waterbirds on these wetlands was determined biannually from 1992 to 2019, with counts conducted from a boat following a standardised route. Historical abundance data from the 1980s was also used to describe long-term abundance changes. Observed seasonality of four herbivorous waterbirds differed from published accounts. Long-term abundance trends indicated a combination of declining, increasing and stable populations which, in several instances, differed from regional (southern African) assessments. Significant long-term decreases have occurred in five herbivorous species in the lakes complex (Common Moorhen Gallinula chloropus, Red-knobbed Coot Fulica cristata, Yellow-billed Duck Anas undulata, Cape Shoveler Anas smithii, Cape Teal Anas capensis), whereas increases have occurred in two species (Spur-winged Goose Plectropterus gambensis, Egyptian Goose Alopochen aegyptiaca). Similar types of change occurred across multiple waterbodies, and in different seasons. The similarity of trends in spatially separated wetlands suggested either high interconnectivity of populations between wetland systems and/or some drivers of change of mobile species being broad scaled and regional, rather than system specific. Local reasons for changes potentially include increasing extent of cultivated fields, a proliferation of emergent macrophytes and loss of open sandbanks, changing food availability, increasing disturbance, and disease.